Small scale gold mining effects on the miners and local communities in semi-arid region of Ethiopia - Meaza, Hailemariam; Ali, Mushir; Hishe, Solomon; Tesfamariam, Zbelo (Journal for Geography, 2015)
North Ethiopian highlands are traditionally known for gold mining which has been means of livelihood of the rural community. The present work was conducted to investigate socio-economic conditions of gold miners, ways of obtaining the gold, their earning and negative consequences of the gold mining. On the basis of random sampling, 140 miners were interviewed. Moreover, focus group discussions transect walks and practical observations across the mining sites were made with team leaders on different issues of gold mining and its effects. Descriptive statistics was used to compute socio-economic characteristics, gold harvesting, and income dynamics. ANOVA was run to observe variations of income from gold mining and other sources, 2009 to 2012. The positive effects of gold mining for involved people were regarding income, employment, expenditure on education, health and food consumption. On the other hand, conflicting interest, communicable diseases, aggressive child labour, school dropouts, social disruptions and injuries were challenges of the small scale gold mining. The findings highlight that the income generated from small scale gold mining plays a pivotal role in reducing rural poverty. Therefore, providing integrated training for gold miners can mitigate the challenges of small scale gold mining and thereby to improve livelihoods of the small scale gold miners in Ethiopia.